FAMILY DEVELOPMENT SESSION SEBAGAI UPAYA PENINGKATAN KETERAMPILAN HIDUP KELUARGA PENERIMA MANFAAT DI KELURAHAN LIDAH WETAN - Ika Purwandia; Sjafiatul Mardliyah (J+PLUS UNESA, 2022)
Family Development Session (FDS) is a structured learning process through mentoring activities to form awareness and change the behavior of KPM. KPM are poor or pre-prosperous families who receive the benefits of the PKH program in the form of Non-Cash Food Assistance (BPNT) and cash. This study aims to determine the implementation and impact of Family Development Session on improving the life skills of Beneficiary Families in Lidah Wetan Village. This research uses descriptive qualitative method. This descriptive qualitative method was chosen in order to describe the real problem or situation without the intervention of the researcher while the research was in progress. Data collection techniques in this study were observation, in-depth interviews and documentation. The results showed that the implementation of family development session activities carried out by PKH facilitators in Lidah Wetan Village was able to have a positive impact on KPM. Changes in behavior experienced by KPM and the usefulness of Family Development Sessions (FDS) in improving KPM life skills are shown by changes in KPM behavior in child care and education, increased KPM knowledge about the importance of improving nutrition and active access to health services (posyandu, puskesmas, clinics, hospital, etc.), KPM is able to set aside some of the income to be saved and used to open a business to increase family income.